Differences in Place Attachment Profiles in Adolescents in the Home and School Environments in the Formation of Self-Identity - Amriwijaya, Julian (Scientia Psychiatrica, 2023)
Introduction: Place attachment influences the way adolescents form their identity. The home and school environments, as the two main environments, provide the foundation for the development of adolescent identity. Positive attachment to both of these environments can provide adolescents with a sense of stability and consistency, helping them understand who they are, where they come from, and what is important to them. This study aimed to explore the place attachment profile of adolescents in the home and school environment in the formation of adolescent self-identity. Methods: This study was a descriptive observational study, where as many as 592 research subjects were observed in this study. Attachment scale observation was carried out using the Bortholomew and Griffin attachment scale questionnaire, where observations were made on four aspects. Results: The attachment aspect that stands out in the attachment to the home environment is the secure attachment aspect. As many as 74.83% of respondents tend to have a place attached to this aspect, in contrast to the attachment aspect, which is prominent in the attachment to the school environment, where the secure attachment aspect still stands out but is not as dominant as the attachment to the home environment. The secure attachment aspect with the school is only 50.34%, and the rest is spread over other aspects of attachment. Conclusion: The place attachment profile of adolescents differs between home and school environments. Adolescents feel more secure (secure attachment) in the home environment than in the school environment.